DAMPAK PANDEMI COVID-19 PADA KESEHATAN PSIKOLOGIS MAHASISWA DALAM PROSES PEMBELAJARAN - Ni Komang Wijiani Yanti (ITKM WIDYA CIPTA HUSADA, 2021)
Anxiety affects student learning outcomes, because it tends to produce confusion and perceptual distortions. Prolonged and persistent anxiety can lead to stress to depression if not treated immediately and this is further increasing in the conditions of the Covid-19 pandemic with online learning methods. The study aims to determine the impact of the Covid-19 pandemic on the psychological health of students in the learning process. This research is quantitative with a descriptive analytic approach with sampling techniques using total sampling on students who undergo an online learning process during the Covid-19 pandemic. The research was conducted on students of the West Nusa Tenggara Nahdlatul Ulama University. Data were collected using a questionnaire related to respondent characteristics, level of anxiety / anxiety, stress and depression using the DASS-21 instrument. he results of the study were analyzed univariately which were presented in a frequency distribution. Based on the characteristics of respondents, of the 235 students on average 19.77 years old and 127 students (54%) were female, the type of learning method that was more popular was face-to-face at 88.1% and the rest online at 11.9%, Most of the obstacles experienced in the online learning process were the need for internet quota (48.5%) and difficulty concentrating in understanding the material (38.7%). The results showed that most of the 235 respondents experienced mild anxiety as many as 99 students (42.13%) and moderate anxiety as many as 38 students (16.17%). The results of research related to stress levels showed that there were some students who experienced mild stress, namely 60 students (25.53%). Based on the depression level, 14 students (6.38%) experienced mild depression due to online learning.